Anthranilate Synthase Enzyme System and Complementation in Pseudomonas Species - Queener, S. F. (1970)
Anthranilate synthase in Pseudomonas putida is a two component enzyme system. The proteins, termed AS I and AS II, have respective molecular weights of 65,000 and 18,000. Five additional Pseudomonas species, both tryptophan requiring and independent strains, were examined and all were shown to contain similar two component systems. Anthranilate formation by „amide transfer,” with L-glutamine as nitrogen donor, requires both proteins; „amination,” utilizing ammonium ion, proceeds at pH 9 with only the larger component, AS I. The product of the P. putida trpA gene, AS I, carries the chorismate binding and tryptophan feedback inhibition sites whereas the smaller component, AS II, functions in glutamine binding. We have not been able to prepare mutants lacking AS II activity nor have other catalytic activities been detected for this protein. The second step unique to tryptophan biosynthesis is catalyzed by phosphoribosyl transferase, in P. putida the trpB gene product. Phosphoribosyl transferase, EC 2.4.2.14, is separable from both AS I and II, and is not required for anthranilate synthesis. This chromosomal and protein organization differs from the array found in the enteric bacteria where phosphoribosyl transferase carries also the AS CoII enzymic activity. Among the six Pseudomonas species examined, two groups may be distinguished on the basis of subunit complementation, the putida-aeruginosa (p-a), and the acidovorans-testosteroni (c-t). Within these groups the hybrid enzymes are equivalent in activity to the native enzyme and the level of subunits required is comparable. Between the groups the hybrid enzymes are lower in activity than either native form. The c-t components separate with difficulty and the aggregate appears to be larger than the more freely dissociable p-a complex. P. stutzeri resembles the p-a class and P. multivorans the c-t class.